Tetracarbonyl (η5-cyclopentadienyl) vanadium Complexes with R3E Substituents (E = Si, Ge, Sn) at the Cp-Ring - Adreas Duch; Martin Hoch; Dieter Rehder (CHIMIA)
The preparation and spectral properties (IR, 1H- and 51V-NMR, MS) of the complexes [(η5-R3EC5H4)V(CO)4], R3E = Me3Si, Et3Ge, Et3Sn and n-Bu3Sn, are described. These compounds are obtained by direct reaction from V(CO)6 and R3EC5H5. The complexes [R3EV(CO)6] are formed as by-products in the case of E = Sn and Ge. With Ph3PbC5H5, the only metalated complex is [Ph3PbV(CO)6].